Distribution and illegal killing of the Endangered Indian pangolin Manis crassicaudata on the Potohar Plateau, Pakistan. Issue 1 (16th May 2017) - Mahmood, Tariq; Akrim, Faraz; Irshad, Nausheen; Hussain, Riaz; Fatima, Hira; Andleeb, Shaista; Aihetasham, Ayesha
Abstract: The Endangered Indian pangolin Manis crassicaudata, a burrowing, armoured mammal, plays an important role in the food web by consuming insects and termites. In Pakistan the species' range includes the 22, 000 km 2 Potohar Plateau, where it is under pressure from illegal hunting for its scales and requires conservation attention. We used a geographical information system to quantify the range of the Indian pangolin on the Plateau and to compare this with the range estimated in the IUCN Red List assessment of the species. We found that the species occupies c. 89% of the Plateau, in eight of the 10 protected areas, compared with the IUCN estimate of 71%, and we recorded the species at 40 locations on the Plateau outside the range predicted by the IUCN assessment. We collected data on the illegal capture and killing of the species, recording 412 individuals that had been killed at 48 locations between January 2011 and the end of April 2013. The highest number of killings was recorded in Chakwal District (n = 156, at 13 sites) followed by the Attock District (n = 149, at eight sites). Although the Indian pangolin's range on the Potohar Plateau is c. 18% larger than that estimated in the IUCN assessment, the species is under pressure from illegal killing and requires urgent conservation measures to save the small remaining population and avoid the extirpation of this vital insectivorous predator from the area.